Beobachtungen in den Hochländern Äthiopiens auf einer Forschungsreise 1953/54 - Werdecker, Josef (ERDKUNDE, 1955)
The principal aim of this field study was to investigate the structure of High Semien in northern Ethiopia. In addition, other subject matter was collected for use in a regional treatise of this mountain region, which attains a height of 4,600 m. approximately. For comparison, observations were made in the Ethiopian rift valley and the Galla highland. Traverses were made from Lake Margherita (1,270 m.) to the Hula Plateau (3,000 m.) and from Lake Zuai (1,800 m.) to Mt. Cilalo (3,900 m.). These clearly showed the zoning of the vegetation from the dry savanna in the lake region through the cultural landscape of the humid savanna, and the rainy mountain forest to the zone of tree-like ERICA ARBOREA and the high pastures in the region of the mountain peaks. Since no detailed map of High Semien existed on which to plot the observations, a terrestrial photogrammetric survey of the central region (the mountains of Ras Dedjen, and Buahit, the Mai Shaha Valley and Amba Ras), an area of about 500 sq. Km., was carried out from which a map on the scale of 1 : 25,000 could be constructed. The survey was based on a geographical determination of location and a local triangulation net which was observed with a Zeiss theodolite. Altitudes were measured with a Paulin aneroid and the height of Ras Dedjen, the highest mountain of Ethiopia, was thus measured to be 4,580 m. This was used as the base height for the construction of the contour plan which in the meantime has been completed on the stereoautograph of the Department of Photogrammetry, Topography and General Cartography of the Technische Hochschule, München. The contour plan provides a precise image of the rugged mountain surface and will, in the future, serve as a valuable base for systematic investigations in High Semien. Hand in hand with the topographical survey went the study of the geomorphological conditions, the climate, the vegetation and the economic conditions. Raised valley floors and erosion surfaces bear witness to the repeated uplift of the old volcanic mountain body. On the evidence of formidable side moraines, which were observed in the great Mai Shaha valley at 2,700 m., one is justified in concluding that glaciation during the Pleistocene period was considerable. The present day climatic snow line would be at an altitude of 4,700—4,800 m., which is above the level of the highest peak. Only during the rainy season a cover of hail and snow of course grain which lasts for some time is formed in high locations. Above 3,600 m., as a result of nightly frost, solifluction, viz. movement of the sods, is clearly observable. Above 4,300 m., in the rock waste zone, which is almost devoid of vegetation, stone strips and polygonal stone rings are found. The vegetation of the mountain heights is characterised by the „mist forest of ERICA ARBOREA and alpine meadows with lobelias and helichrysum bushes. Up to a maximum of 3,800 m., the high plateaux and the more level sections of the valleys are cultivated by the Amhari, a largely agricultural people. The main crop is barley. Above 3,800 m., pasturing, mainly of sheep, plays a certain role. Settlement is relatively dense, the highest hamlets being situated at about 3,700 m.